Optimalisasi Potensi E-Commerce di Kabupaten Sorong : Peran Pemerintah dalam Meningkatkan Keterlibatan UMKM Lokal - Tamaya, Selvia; Purnomo, Arie; Fikri, Awal (Jurnal Fase Kemajuan Sosial dan Politik: Faksi, 2024)
This research aims to describe and analyze the optimization of e-commerce potential in Sorong district. The government's role in increasing the participation of local MSMEs (Micro, Small and Medium Enterprises). In this research the author uses the concepts of innovation, MSME economics, public policy and social media. This research method uses a qualitative descriptive approach with five informants. Data collection techniques were carried out through observation, interviews and literature studies. Based on the following findings: The government as a regulator, facilitator and facilitator who provides a legal basis can help improve Solon by facilitating financing and market platforms and increasing production and sales to a wider audience in the district. The government also provides training and support for e-commerce adoption through technical guidance and outreach, including marketing and product curation, as well as the involvement of regional MSME groups.